Chemical characterization of White Burley tobacco stems at varying elevations for bio-oil optimization using FTIR - Puspitasari, Risky Anggraeni; Dewanti, Beauty Suestining Diyah; Setiyawan, Hendrix Yulis (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
Tobacco stems (Nicotiana tabacum), often discarded as waste, have significant potential as a source of secondary metabolites, including bio-oil. This study examines the effect of elevation on the chemical composition of White Burley tobacco stems from lowland, midland, and highland regions in Lumajang District using Fourier Transform Infrared Spectroscopy (FTIR). The FTIR results revealed distinct variations in functional groups: the lowland sample showed strong O–H, C–H aliphatic, C=O, and C–O peaks, indicating the presence of oxygenated compounds typical of bio-oil. The midland sample exhibited O–H, C–H aliphatic, and C–O–C bands, suggesting volatile organic and polar compounds. The highland sample revealed O–H, C–H, C=O, and C–O peaks, indicating both polar and non-polar compounds. Physicochemical analysis of aqueous extracts prepared from the same lowland, midland, and highland stem samples showed that the pH values were similar across samples (8.35–8.59), with the lowland sample having the lowest density (1.032 g/mL). These attributes suggest the lowland sample is most favorable for bio-oil production due to its closer pH to diesel oil and lower density. The findings indicate that elevation influences tobacco stem metabolites and physical properties, with lowland stems showing the greatest potential for high-quality bio-oil production.